(Upaya Meningkatkan Kemampuan Konsep Matematika Awal Pada Anak Usia 4-5 Tahun Menggunakan Media Papan Flannel) - Alawiyah, Tuti (Lembaga Penelitian dan Pendidikan Mandala, 2023)
. In general, students who are compiling their thesis often experience difficulties. The difficulties encountered are very diverse, ranging from a lack of understanding of the problem to be studied, limited references, lack of mastery of theory, not having the desire to start writing, being busy working, and so on. This study aims to analyze the difficulties of seventh semester students in writing scientific papers. This type of research is descriptive research with a qualitative approach. Subject This research is students of seventh semester (semester VII) or final year who are under thesis guidance. Data collection techniques in this study using a questionnaire. A difficulty questionnaire was administered to students who were writing their thesis. Data analysis techniques using percentage techniques are then described. The results of the research generally obtained information that students had difficulty in putting ideas into scientific writing, namely around 58.47%. The use of statistics in data processing is a percentage of 41.64%, and the telling of research results is a percentage of 54.17%. The results of the research are expected to be input, information and reference for all students of the Faculty of Culture, Management and Business of the Mandalika University of Education so that the difficulty factor for students in completing thesis can be overcome.